Konflik Sosial Pendekatan Sosiologi dan Antropologi Hukum Keluarga Islam (HKI) - Huzaini, Huzaini (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Conflict is the phenomenon that often arises because conflict has always been a social and political part of human life and a driving force in socio-political dynamics and change. Conflict has positive and negative impacts, the positive impact of social conflict is that conflict facilitates the achievement of reconciliation of various interests. This research method uses qualitative research with the type of literature review research that will describe, explain and analyze related research. The results of this study are to analyze the good impact on the progress and change of society, but there are some conflicts that actually have a negative impact causing damage, creating instability, disharmony and insecurity and even causing casualties. Today conflicts often occur in various elements of society. This is due to various cultural backgrounds and socio-economic status. This is often used by politicians to create internal solidarity and integration. The leader creates a situation as if there is a common enemy, so that society tends to be integrative. However, if what is considered a common enemy does not exist, then community solidarity tends to weaken and not infrequently disintegrates. Therefore, the leader will continue to create conflict.